On Heartbleed: A Hard Beginnyng Makth a Good Endyng. - Paterson, Kenny (Communications of the ACM, 2018)
The author discusses the article "Analysis of SSL Certificate Reissues and Revocations in the Wake of Heartbleed" by Liang Zhang et al. in this issue. He mentions the issues of OpenSSL software,public key security, and the revocation and replacement of digital certificates.